Upaya Hukum Keberatan terhadap Putusan Badan Penyelesaian Sengketa Konsumen (BPSK) - Supianto Supianto (JURNAL RECHTENS, 2013)
One of the efforts to resolve disputes that arise between businesses and the consumers, the government established the Consumer Dispute Settlement Body (BPSK). BPSK formed to handle the settlement of consumer disputes based on the principle of efficient, fast, inexpensive and professional. Any consumer who feels aggrieved by the business can file complaints through Consumer Dispute Settlement Body (BPSK). Settlement of consumer disputes filed with the BPSK must be completed no later than twenty-one working days after the claim is received by BPSK. At the end of the settlement process, the results are set forth in a BPSK decision which is final and binding. Against this decision, the parties do not accept or not satisfied with the content of BPSK decision may appeal to the District Court.